Immunotherapy in Glioblastoma: Why promising strategies fail to improve survival - Osama Salar; Mehar Masroor; Kanchan Chaudhary; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2026)
Immunotherapy has transformed the management of several extracranial malignancies; however, its efficacy in GBM has been limited. Large clinical trials evaluating immune checkpoint inhibitors have failed to demonstrate meaningful survival benefit in newly diagnosed and recurrent GBM. Other modalities, including dendritic cell vaccines, chimeric antigen receptor (CAR) T-cell therapies, and oncolytic virotherapy, have shown encouraging but modest results in selected patients. This narrative review summarizes the current role of immunotherapy in GBM, focussing on its impact on patient outcomes, underlying barriers to therapeutic success, and future directions. Keywords: Glioblastoma; Immunotherapy; Oncolytic virotherapy; Dendritic cell vaccine.